Mechanics and Physics of Precise Vacuum Mechanisms - Deulin, E. A.; Mikhailov, V. P.; Panfilov, Yu V.; Nevshupa, R. A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
In this book the Russian expertise in the field of the design of precise vacuum mechanics is summarized. A wide range of physical applications of mechanism design in electronic, optical-electronic, chemical, and aerospace industries is presented in a comprehensible way. Topics treated include the method of microparticles flow regulation and its determination in vacuum equipment and mechanisms of electronics; precise mechanisms of nanoscale precision based on magnetic and electric rheology; precise harmonic rotary and not-coaxial nut-screw linear motion vacuum feedthroughs with technical parameters considered the best in the world; elastically deformed vacuum motion feedthroughs without friction couples usage; the computer system of vacuum mechanisms failure predicting. This English edition incorporates a number of features which should improve its usefulness as a textbook without changing the basic organization or the general philosophy of presentation of the subject matter of the original Russian work. Experience at the Bauman Moscow State Technical University and other schools shows that the book will be useful to engineering students who wish to prepare for more advanced studies and applications of vacuum science, technology and its applications.
Using Precise Mechanisms in Modern Vacuum Technological Equipment -- Typical Vacuum Mechanisms -- Friction in Vacuum -- Matrix Method of the Design of New Mechanisms Structure -- Precision of Vacuum Mechanisms -- Vacuum Mechanisms of Nanoscale Precision -- Ultrahigh Vacuum Rotary-Motion Feedthroughs -- Ultrahigh Vacuum Non-Coaxial Linear-Motion Feedthroughs -- Vacuum Frictionless Mechanisms Based on the Principle of Controlled Elastic Deformation -- Flow of Microparticles Originating from Mechanisms in Vacuum.
Keywords: Engineering; Vibration; Engineering design; Chemistry, inorganic; Surfaces (Physics).; Engineering; Engineering Design; Engineering, general; Tribology, Corrosion and Coatings; Surfaces and Interfaces, Thin Films; Vibration, Dynamical Systems, Control